2019
DOI: 10.1007/s42757-019-0049-3
|View full text |Cite
|
Sign up to set email alerts
|

A review on bubble generation and transportation in Venturi-type bubble generators

Abstract: Venturi-type bubble generators own advantages of simplicity in structure, high efficiency, low power consumption, and high reliability, exhibiting a broad application potential in various fields. This work presents a literature review of recent progress in the research concerning Venturi-type bubble generators, with a focus on the performance evaluation, bubble transportation, and breakup mechanisms. Experimental studies employing flow visualization techniques have played an important role in exploring the bub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 83 publications
(128 reference statements)
1
27
0
Order By: Relevance
“…Their main conclusion is that throat length/throat diameter ratio and diverging angle play key roles in determination of the performance of a Venturi-type bubble generator. For the l/d ratio, the results from Reichmann et al [9] and Huang et al [10] showed that bubble diameter reduced with higher l/d ratio while the results from Unyaphan et al [18] did not support this conclusion. For the diverging angle, Lee et al [19] and compared the bubble diameter produced from five Venturi tubes with different diverging angles in the range of 15 • -45 • .…”
Section: The Effect Of Geometrical Parameters On Average Bubble Diameter and Bubble Diameter Distributionmentioning
confidence: 93%
See 3 more Smart Citations
“…Their main conclusion is that throat length/throat diameter ratio and diverging angle play key roles in determination of the performance of a Venturi-type bubble generator. For the l/d ratio, the results from Reichmann et al [9] and Huang et al [10] showed that bubble diameter reduced with higher l/d ratio while the results from Unyaphan et al [18] did not support this conclusion. For the diverging angle, Lee et al [19] and compared the bubble diameter produced from five Venturi tubes with different diverging angles in the range of 15 • -45 • .…”
Section: The Effect Of Geometrical Parameters On Average Bubble Diameter and Bubble Diameter Distributionmentioning
confidence: 93%
“…Their main conclusion is that throat length/throat diameter ratio and diverging angle play key roles in determination of the performance of a Venturi-type bubble generator. For the l/d ratio, the results from Reichmann et al [9] and Huang et al [10] showed that bubble diameter reduced with higher l/d ratio while the results from Unyaphan et al [18] did not support…”
Section: The Effect Of Geometrical Parameters On Average Bubble Diameter and Bubble Diameter Distributionmentioning
confidence: 93%
See 2 more Smart Citations
“…Air bubble generation technology has been used to improve vehicle efficiency by reducing fuel consumption and reducing the fuel-air ratio [1]. Many studies were focused on the size distribution of air bubbles measurements to control air-fuel mixing by applying the liquid and airflow rates [2]. Bubble transportation and mechanisms of bubble breakup were also studied.…”
Section: Introductionmentioning
confidence: 99%